Work and Cancer Survivors - Feuerstein, Michael; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Work and Cancer Survivors Edited by Michael Feuerstein, Uniformed Services University of the Health Sciences, Bethesda, Maryland Cancer survivors are returning to the workplace in higher numbers than ever before. This is a positive outcome of the "war on cancer", however, many of these cancer survivors face the possibility of illness- or treatment-related complications; employer discrimination or harassment; and other serious concerns. Work and Cancer Survivors reviews many of the issues relevant to cancer survivors in the workplace from the survivors$1 (B, employers$1 (B, and global perspectives. This interdisciplinary volume brings together experts in fields as varied as epidemiology, economics, rehabilitation, psychology, ergonomics, law and public policy to create a unique, up-to-date reference of what is currently known and what needs to be considered in the future. With this knowledge, challenges faced by this growing population can be better addressed by health care providers, employers, survivors and their families. Among the topics covered: The significance of work for survivors. Economic burden. Factors affecting work, including pain, fatigue, and cognitive limitations. Primary and occupational health care approaches, rehabilitation, and workplace accommodation. Legal and policy issues. Work concerns specific to young cancer survivors. International efforts and Policy development. In addition to its value to researchers and clinicians working with cancer survivors, the book has immediate salience to professionals and students in behavioral medicine and health psychology, psychiatry, public health, physical and occupational therapy, vocational rehabilitation and social work. As treatment outcomes improve and the workforce continues to age, the information in Work and Cancer Survivors will only gain in relevance.s
Section I Introduction -- Chapter 1 Work in cancer survivors -- Section II Epidemiology -- Chapter 2 Descriptive epidemiology of return to work and work limitations: Prevalence and patterns among various cancer types -- Chapter 3 Qualitative studies of work in cancer survivors -- Chapter 4 Factors impacting work -- Chapter 5. Burden of work: Economic analyses -- Section III Models -- Chapter 6 Models of work and cancer survivors -- Section IV Measurement -- Chapter 8 Methods used to measure work productivity in chronic illness -- Section V Management -- Focus on survivor -- Chapter 10 Assessment of factors associated with work: Clinic and Workplace -- Chapter 11 Medical management -- Chapter 12 Physical therapy and exercise -- Chapter 13 Biobehavioral management -- Focus on workplace -- Chapter 15: Employer concerns -- Chapter 16 Workplace accommodation and ergonomics -- Chapter 17 Legal and policy matters -- Section VI Future Directions -- Chapter 18. Research, Clinical and Policy Needs.
Keywords: Medicine; Oncology; Rehabilitation; Labor economics; Demography; Medicine & Public Health; Rehabilitation; Public Health/Gesundheitswesen.; Oncology; Labor Economics; Demography